DETERMINANTS OF PREVENTIVE BEHAVIOR REGARDING CARDIOVASCULAR DISEASES AND RISK FACTORS IN PATIENTS WITH ESSENTIAL HYPERTENSION AND CHRONIC ISCHEMIC HEART DISEASE - D. Yu. Platonov; T. A. Kostjuk; A. I. Brandt; O. V. Tsygankova (Рациональная фармакотерапия в кардиологии)
Aim. To analyze potential determinants of preventive behavior (PB) in patients with essential hypertension (HT) and chronic ischemic heart disease (CIHD), and to establish their significance and hierarchy. Material and methods. Patients with HT (n=285) and CIHD (n=223) were studied. Questioning of all patients was performed to assess the characteristics of their PB. Differentiated multivariate analysis of activity and efficacy of PB determinants was performed in HT and CIHD patients by the method of step-by-step backward logistic regression. Results. Awareness of the cardiovascular diseases (CVD) and its prevention (odds ratio [OR] 6.08) as well as high level of general education (OR=2.29) were the most significant determinants of active PB in HT patients. Sufficient social support (OR=3.77), awareness of CVD and its prevention (OR=3.16) were the most significant determinants of active PB in patients with CIHD. Efficacy of PB in patients with HT and CIHD mostly depends on satisfaction of medical service (OR=10.2 and 6.63, respectively), social support (OR=6.25 and 10.5, respectively), adequate awareness of CVD and its prevention (OR, 6.92 and 6.64, respectively). Conclusion. PB activity and efficacy in patients with HT and CIHD depends on many contributing and impeding factors. Disregarding these factors can result in failure in preventive efforts at both individual and population levels.